Increasing brand recall for naming rights sponsorships - Donovan, Robert; Anwar-McHenry, J.; Hernandez Aguilera, Y.; Nicholas, A.; Kerrigan, S. (Emerald Group Publishing, 2016)
© 2016, © Emerald Group Publishing Limited.Purpose: Maximising return on naming rights sponsorships is important for social marketing campaigns with limited funds. Naming rights allow the sponsor’s brand to be aligned with the event name in text and visual promotional materials. For visual displays, either the brand logo or the brand name in words can be aligned with the event name. As the Act–Belong–Commit mental health promotion campaign’s logo encapsulates the brand name, a study was conducted to assess the relative impact on recall of “Act–Belong–Commit” as part of a sponsored event name, when the logo was aligned with the event name versus when the brand name in only words was aligned with the event name. Design/methodology/approach: An intercept survey was conducted with n = 112 adult university students. Participants were presented with one of the above two branding alignments for the sponsored event. The image was removed from view, a distracter question asked and participants were asked to recall the name of the event. Findings: Recall of the Act–Belong–Commit brand in full as part of the name of the event was significantly and substantially greater for participants exposed to the words only alignment versus the logo alignment: 52 vs 7 per cent (p < 0.000). Practical implications: Given these findings, the campaign has adopted the policy of using the words Act–Belong–Commit alongside the event name rather than the logo in future naming rights sponsorships. Originality/value: It is recommended that other social marketing brands with similar brand/logo designs undertake research to ensure optimal return on naming rights sponsorships.